Inhibition of TGF- β- Receptor signaling augments the antitumor function of ROR1-specific CAR T-cells against triple-negative breast cancer - Stuber, Tanja; Monjezi, Razieh; Wallstabe, Lars; Kuehnemundt, Johanna; Nietzer, Sarah Louise; Dandekar, Gudrun; Woeckel, Achim; Einsele, Hermann; Wischhusen, Joerg; Hudecek, Michael (Journal for ImmunoTherapy of Cancer, 2020)
Background Immunotherapy with chimeric antigen receptor (CAR)-engineered T-cells is effective in some hematologic tumors. In solid tumors, however, sustained antitumor responses after CAR T-cell therapy remain to be demonstrated both in the pre-clinical and clinical setting. A perceived barrier to the efficacy of CAR T-cell therapy in solid tumors is the hostile tumor microenvironment where immunosuppressive soluble factors like transforming growth factor (TGF)-β are thought to inhibit the cellular immune response. Here, we analyzed whether CAR T-cells specific for the receptor tyrosine kinase-like orphan receptor 1 (ROR1) antigen, that is frequently expressed in triple-negative breast cancer (TNBC), are susceptible to inhibition by TGF-β and evaluated TGF-β-receptor signaling blockade as a way of neutralizing the inhibitory effect of this cytokine. Methods CD8 + and CD4 + ROR1-CAR T-cells were prepared from healthy donors and their antitumor function analyzed using the TNBC cell line MDA-MB-231 in vitro and in a microphysiologic 3D tumor model. Analyses were performed in co-culture assays of ROR1-CAR T-cells and MDA-MB-231 cells with addition of exogenous TGF-β. Results The data show that exposure to TGF-β engages TGF-β-receptor signaling in CD8 + and CD4 + ROR1-CAR T-cells as evidenced by phosphorylation of small mothers against decapentaplegic homolog 2. In the presence of TGF-β, the cytolytic activity, cytokine production and proliferation of ROR1-CAR T-cells in co-culture with MDA-MB-231 TNBC cells were markedly impaired, and the viability of ROR1-CAR T-cells reduced. Blockade of TGF-β-receptor signaling with the specific kinase inhibitor SD-208 was able to protect CD8 + and CD4 + ROR1-CAR T-cells from the inhibitory effect of TGF-β, and sustained their antitumor function in vitro and in the microphysiologic 3D tumor model. Combination treatment with SD-208 also led to increased viability and lower expression of PD-1 on ROR1-CAR T-cells at the end of the antitumor response. Conclusion We demonstrate the TGF-β suppresses the antitumor function of ROR1-CAR T-cells against TNBC in preclinical models. Our study supports the continued preclinical development and the clinical evaluation of combination treatments that shield CAR T-cells from TGF-β, as exemplified by the TGF-β-receptor kinase inhibitor SD-208 in this study.
CRIS-Team Scopus Importer:2023-03-23
Keywords: breast neoplasms; chimeric antigen; immunotherapy; receptors